If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -2) + 3(2x + 1) = 26 Reorder the terms: 5(-2 + x) + 3(2x + 1) = 26 (-2 * 5 + x * 5) + 3(2x + 1) = 26 (-10 + 5x) + 3(2x + 1) = 26 Reorder the terms: -10 + 5x + 3(1 + 2x) = 26 -10 + 5x + (1 * 3 + 2x * 3) = 26 -10 + 5x + (3 + 6x) = 26 Reorder the terms: -10 + 3 + 5x + 6x = 26 Combine like terms: -10 + 3 = -7 -7 + 5x + 6x = 26 Combine like terms: 5x + 6x = 11x -7 + 11x = 26 Solving -7 + 11x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 11x = 26 + 7 Combine like terms: -7 + 7 = 0 0 + 11x = 26 + 7 11x = 26 + 7 Combine like terms: 26 + 7 = 33 11x = 33 Divide each side by '11'. x = 3 Simplifying x = 3
| -1-3=y | | 2x-35=6x+2 | | 2x+2-4=2/3 | | 15x+45=30 | | (2x-3)(2x+3)=135 | | -27+4x=7x+48 | | -2x^2+3x+9= | | 6-2x=-7+6 | | 4-n=10 | | -8x^2+9x+5= | | 8x-14=22 | | 99x+100=1 | | x^2+4x+4=44 | | 4a-1/3-3(a-2)=2 | | x-2y+3z=4 | | 14c+2=4 | | 2a+5=-2 | | 2x^2=22.126*22.125 | | -8=z/4 | | 6.6+x=0.9 | | 5d-3-3d=13 | | y=-32 | | 4b^2-36b+81=0 | | 2+x=x-2 | | 7r-4-8r=5 | | ab-9a+9b-81= | | 8n+2-9n=-8 | | 10x+15=8x+35 | | 5a^2-22a+8= | | (3x+2)(x+5)= | | 6x+1-3x=10 | | a-2-2a=10 |